Cancellation performance of co-site antenna interference cancellation system for AM interference - Yunhao JIANG; Nan ZHAO; Cong LIU; Wenfang DING; Ziqiang XI (Tongxin xuebao)
The interference cancellation performance of actual co-site antenna interference cancellation system (CICS) under amplitude modulation jamming signal was analyzed.The expressions of the steady-state weights and theirs structure characteristics of the interference cancellation system under the AM signal were given.The formulae of the interference cancellation ratio (ICR) for carrier frequency and side frequency were derived.The influence factors and the influence rules of the ICR were analyzed.The steady state weights of the interference cancellation system (ICS) were the weighting of the carrier frequency optimal weights and the edge frequency optimal weights according to the power ratio.The increase of the signal bandwidth will increase the discreteness of the carrier frequency optimal weights and the edge frequency optimal weights and lead to the decrease of the interference cancellation ratio (ICR).The decrease degree of the edge frequency ICR was greater than that of the carrier frequency ICR.To improve ICR by increasing the gain was limited.The relationship between the interference cancellation ratio limit and the equivalent transmission delay was given.The design method of the interference cancellation system to improve the ICR under the AM signal was proposed.Finally,the correctness and validity of the theoretical analysis was verified by simulation.